Recent trends in Australian percutaneous coronary intervention practice: Insights from the melbourne interventional group registry - Yan, B.; Ajani, A.; Clark, D.; Duffy, S.; Andrianopoulos, N.; Brennan, A.; Loane, P.; Reid, Christopher (2011)
Objective: To evaluate percutaneous coronary intervention (PCI) practice trends and 12-month outcomes in Australia in the era of drug-eluting stents (DES). Design, setting and patients: Prospective study of consecutive patients undergoing 9204 PCIs between 1 April 2004 and 31 March 2008 at seven Victorian public hospitals. Main outcome measures: Temporal trends in baseline characteristics and in-hospital and 12-month clinical outcomes including death, myocardial infarction (MI), target vessel revascularisation (TVR) and composite major adverse cardiac events (MACE), from year to year. Results: Between 2004-2005 and 2007-2008, the mean age of patients undergoing PCI was stable (65 ±12 years), and comorbidities such as hypertension, hyperlipidaemia, peripheral arterial disease and stroke increased (P<0.05). There were fewer elective and more urgent PCIs, especially for MI < 24 hours (17.6% in 2004-2005 to 27.2% in 2007- 2008, P < 0.01). Overall stent use remained high (mean, 94.6%), but use of DES declined steadily (53.9% in 2004-2005 to 32.0% in 2007-2008, P < 0.01), despite increases in complex lesions. Planned clopidogrel therapy of = 12 months after insertion of DES increased from 54.7% in 2004-2005 to 98.0% in 2007-2008 (P < 0.01). The overall procedural success rate was high (mean, 95.9%), and 12-month rates of mortality (3.8%), MI (4.8%), TVR (6.8%) and stent thrombosis (1.8%) remained low. Selective use of DES was an independent predictor of freedom from MACE at 12 months (odds ratio, 0.68; 95% CI, 0.56-0.81). Conclusions: Use of DES declined steadily from 2004-2005 to 2007-2008, despite increasing patient risk profile and lesion complexity. Procedural success remained high and 12-month adverse outcomes remained low, with increasing use of prolonged dual antiplatelet therapy.